Fibromodulin and regulation of the intricate balance between myoblast differentiation to myocytes or adipocyte‐like cells. Issue 2 (4th January 2018) - Ju Lee, Eun; Tasleem Jan, Arif; Hassan Baig, Mohammad; Ahmad, Khurshid; Malik, Adeel; Rabbani, Gulam; Kim, Taeyeon; Lee, In‐Kyu; Ho Lee, Yong; Park, So‐Young; Choi, Inho
Abstract : Interactions between myoblasts and the surrounding microenvironment led us to explore the role of fibromodulin (FMOD), an extracellular matrix protein, in the maintenance of myoblast stemness and function. Microarray analysis of FMODkd myoblasts and in silico studies were used to identify the top most differentially expressed genes in FMODkd, and helped establish that FMOD‐based regulations of integral membrane protein 2a and clusterin are essential components of the myogenic program. Studies in knockout, obese, and diabetic mouse models helped characterize the operation of a novel FMOD‐based regulatory circuit that controls myoblast switching from a myogenic to a lipid accumulation fate. FMOD regulation of myoblasts is an essential part of the myogenic program, and it offers opportunities for the development of therapeutics for the treatment of different muscle diseases.—Lee, E. J., Jan, A. T., Baig, M. H., Ahmad, K., Malik, A., Rabbani, G., Kim, T., Lee, I.‐K., Lee, Y. H., Park, S.‐Y., Choi, I. Fibromodulin and regulation of the intricate balance between myoblast differentiation to myocytes or adipocyte‐like cells. FASEB J. 32, 768–781 (2018). www.fasebj.org